1981
DOI: 10.1128/aac.20.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acyclovir against mouse cytomegalovirus in vivo

Abstract: Acyclovir reduced mortality and organ virus titers in mice inoculated intraperitoneally with 10 50% lethal doses of mouse cytomegalovirus. This susceptibility to acyclovir of a herpesvirus which lacks thyrnidine kinase is surprising. Alternative phosphorylating enzymes may account for this susceptibility.Acyclovir [ACV; acycloguanosine, 9-(2-hydroxyethoxymethyl)guanine] is a purine analog which has demonstrable inhibitory activity against several members of the herpesvirus group, including herpes simplex virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…While lethal MCMV disease in immunocompetent BALB/c mice is attributed to liver damage culminating in a severe hepatitis within the first week of infection (69), factors contributing to this disease have not been characterized. Disease is prevented by administration of antiviral drugs, revealing a critical contribution of ongoing viral replication (81). Unlike other forms of hepatitis, tumor necrosis factor (TNF) is dispensable for disease in BALB/c mice (70).…”
mentioning
confidence: 99%
“…While lethal MCMV disease in immunocompetent BALB/c mice is attributed to liver damage culminating in a severe hepatitis within the first week of infection (69), factors contributing to this disease have not been characterized. Disease is prevented by administration of antiviral drugs, revealing a critical contribution of ongoing viral replication (81). Unlike other forms of hepatitis, tumor necrosis factor (TNF) is dispensable for disease in BALB/c mice (70).…”
mentioning
confidence: 99%
“…Because the viral TK appeared to be necessary for the phosphorylation of ACV leading to accumulation of acyclo-GTP in infected cells and expression of its anti-HSV effect, it was not surprising to find that human cytomegalovirus, a herpesvirus that does not encode for a TK, is much less sensitive to ACV (7). In contrast, the finding that mouse cytomegalovirus (MCMV), another herpesvirus lacking a TK (10, 21), is almost as sensitive to ACV in vitro and in vivo as is HSV was unexpected (2,28). Even when grown in TK-negative host cells, the replication of MCMV is sensitive to ACV, indicating a mechanism not dependent on cellular or viral TK for converting ACV to its active form (2).…”
mentioning
confidence: 99%
“…However, administration of a single dose of cyclophosphamide (CP) 24 h after virus inoculation induced diffuse interstitial pneumonitis not seen with either virus or CP alone (9). In the studies reported here, we compared the effects of ACV with those of another related antiviral purine analog, 9-(1,3-dihydroxy-2-propoxymethyl)guanine (DHPG), on MCMV replication in lung tissues and on the evolution of interstitial pneumonitis after administration of virus and CP (1,2,7,12). In addition, we compared the antiviral activities of these two compounds on MCMV replication in vitro.…”
mentioning
confidence: 99%